(untitled) (Texas Journal of Medical Science, 2022)
Recent studies have demonstrated a high risk of kidney damage and associated cardiovascular complications in patients with rheumatoid arthritis (RA), which generally determines the prognosis of these patients. However, the frequency of chronic kidney disease (CKD) in RA in the Uzbekistan cohort of patients has not been precisely established. The unfavorable prognostic significance of kidney damage in rheumatoid arthritis (RA) has been actively attracting the attention of researchers in recent years. Certain clinical variants of involvement of the kidneys in the pathological process in rheumatoid arthritis are noted in most patients. Various variants of kidney damage in rheumatoid arthritis are described, in particular, glomerulonephritis, amyloidosis, vasculitis, as well as iatrogenic forms (analgesic tubulopathy, membranous nephropathy, etc.). It is noteworthy that in real clinical conditions, morphological verification of renal pathology may not be performed for a long time in such patients for a number of objective reasons. Early manifestations of functional renal disorders, especially with their moderate severity, do not always attract the attention of clinicians, while the progression of chronic kidney disease (CKD) in RA can be rapid, especially in old age, as well as in association with cardiovascular pathology. The formation of nephropathy in RA has a complex multifactorial character and manifests itself in various clinical and morphological variants. Thus, various clinical forms of kidney damage in RA are known (amyloidosis, glomerulonephritis, less often rheumatoid granulomatosis and rheumatoid renal vasculitis), as well as iatrogenic, due to ongoing treatment (medicinal tubulointerstitial nephritis, membranous nephropathy, mesangioproliferative glomerulonephritis). At the same time, in real clinical practice, the nosological diagnosis of kidney disease in RA is usually established when clinical and laboratory criteria appear, the most important of which is proteinuria, at the same time, it has recently been established that with a low-symptomatic course, renal dysfunction can develop without the presence of proteinuria. It is noteworthy that rheumatologists do not always pay attention to the early manifestations of functional renal disorders, especially with moderate severity of proteinuria, although the rate of decline in kidney function in RA can be quite fast, especially in old age and in association with cardiovascular pathology